2019
DOI: 10.1038/s41467-019-12208-3
|View full text |Cite
|
Sign up to set email alerts
|

Highly structured homolog pairing reflects functional organization of the Drosophila genome

Abstract: Trans-homolog interactions have been studied extensively in Drosophila, where homologs are paired in somatic cells and transvection is prevalent. Nevertheless, the detailed structure of pairing and its functional impact have not been thoroughly investigated. Accordingly, we generated a diploid cell line from divergent parents and applied haplotype-resolved Hi-C, showing that homologs pair with varying precision genome-wide, in addition to establishing trans-homolog domains and compartments. We also elucidate t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
77
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(81 citation statements)
references
References 78 publications
(114 reference statements)
4
77
0
Order By: Relevance
“…Since PSS is thought to be dependent upon homolog pairing, the different properties of the five insertion sites could be due to differences in the strength of local homolog pairing. To investigate this possibility, we took advantage of a recent genome-wide study that measured interaction frequencies between homologs at the embryo stage [ 64 ]. However, analysis of the available Hi-C data did not show any significant correlations (Additional file 2 ).…”
Section: Resultsmentioning
confidence: 99%
“…Since PSS is thought to be dependent upon homolog pairing, the different properties of the five insertion sites could be due to differences in the strength of local homolog pairing. To investigate this possibility, we took advantage of a recent genome-wide study that measured interaction frequencies between homologs at the embryo stage [ 64 ]. However, analysis of the available Hi-C data did not show any significant correlations (Additional file 2 ).…”
Section: Resultsmentioning
confidence: 99%
“…As the male chrX is the only chromosome without a paired homologue, we asked if this male chrX peculiarity may affect the observed differences in the interaction decay profile. To this concern, recent independent studies presenting haplotype-resolved Hi-C data show that the ratio of inter-homologous interactions vs cis -interactions increases at mid-/long-range distances 38,39 . Thus, the lack of a homologous chromosome may result in less mid-/long-range contacts being detected, i.e.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, to definitely disentangle the contribution of homologous chromosomes pairing to the interaction decay profile, we applied polymer folding simulation techniques. Abed et al 39 reported that the level of pairing is correlated to the local chromatin state, which in turn is known to affect the pattern of Hi-C contacts 16,4042 . Therefore, we applied a polymer folding simulation model accounting for chromatin states annotations in the D. melanogaster genome as well as distribution of homologous tight pairing parameters in line with Abed et al 39 estimations (see Methods).…”
Section: Resultsmentioning
confidence: 99%
“…The addition of Hi-C increased switch errors in particular by 0.0126 errors/site. This is likely a consequence of somatic chromosome pairing in dipterans ( 30 ), which has previously been demonstrated to create an excess of sister chromosome contacts in Hi-C data ( 9 , 31 ). The increased switch error rate suggests that ∼17% of Illumina-phasable blocks that are joined by the addition of Hi-C result in switch errors.…”
Section: Resultsmentioning
confidence: 97%